Adenotonsillectomy in children. Issue 1 (January 2020) - Elsayed, Mahmoud; Alhasani, Wiaam; Sudarshan, Purushothaman; Leong, Lisa; Hurley, Matthew; Daniel, Mat
Abstract: Adenotonsillar disorders are a frequent complaint in children and adenotonsillectomy is one of the commonest surgical procedures. The two main indications for adenotonsillectomy are recurrent tonsillitis and obstructive sleep apnoea (OSA). Both are associated with significant morbidity. How best to diagnose OSA is currently unclear. Some centres routinely use sleep studies whilst others rely on history alone. Intracapsular subtotal tonsillectomy, as opposed to complete tonsillectomy, is a good choice in OSA. It is as effective in relieving obstruction but typically has lower morbidity with less pain and bleeding. Postoperative complications are relatively common, and good pain management is essential. There is controversy about effectiveness of tonsil and adenoid surgery, with on-going arguments for and against. Appropriate patient selection based on clinical need and evidence, rather than rationing, is essential.